(untitled) (Research, Society and Development, 2024)
The research is part of a retrospective experience of implementing screening teleconsultations for various medical specialties through the Management Application system for University Hospitals - AGHUx. The objective was to present a study reporting the experience of establishing teletriage in the virtual telemedicine outpatient clinic to reduce the number of patients on the waiting list, for the specialties of pulmonology, cardiology, dermatology, psychiatry and geriatrics. Over the course of 12 months from January to December 2023, 06 waiting lists for medical specialties were “cleaned” with a total of 1,578 patients with a high/very high priority for care, which is why teleconsultation was chosen. During the period, the outpatient specialties selected for this purpose were: Dermatology, Psychiatry, Pulmonology, Cardiology and Geriatrics. Resulting in a total of 608 teleconsultations, including 86 Dermatology, 161 Psychiatry, 117 Pulmonology, 202 Cardiology and 42 Geriatrics. Cardiology 33.2% obtained the highest percentile and the lowest 6.9% was geriatrics. Therefore, the implementation of teletriage is a successful strategy for managing queues in institutions, thus becoming a relevant and supportive factor so that it can contribute to the correct follow-up of the treatment of these patients, an appropriate indication for the highly complex service and thus relieve the system and open new vacancies for first care patients.